Production of Online Word‐of‐Mouth: Peer Effects and the Moderation of User Characteristics. Issue 7 (21st February 2019) - Wang, Yang; Goes, Paulo; Wei, Zaiyan; Zeng, Daniel
Abstract : We study peer effects on individuals' contributions to a major form of word of mouth—online reviews. Provided by either consumers or third‐party professionals, online reviews influence consumer purchasing decisions and hence sales. Individuals have conflicting incentives of free riding and contributing to social capital when writing reviews. We leverage a "natural experiment, " which led to an exogenous expansion in the user population of a major online review platform, to better understand the trade‐off. Our empirical findings are mainly twofold. First, we find that a larger population of audience and peer review writers, an immediate consequence of the exogenous shock, cause individuals to write more reviews with higher quality and assign higher but also more diverse ratings. In addition, we find heterogeneity in peer effects by user activeness, expertise, and popularity. Our findings have implications for companies in managing online feedbacks and for platforms that rely on user contributions.